Inventory and compatibility of marine cadastre in the marine conservation area zoning (case study: Pulau Weh Nature Tourism Park) - Zariansyah Zariansyah; Sugianto Sugianto; Muhammad Rusdi; Muhammad Irham; Faisal Abdullah (Depik, 2024)
This quantitative research presents the classification of marine cadastres in the marine conservation area of Pulau Weh Nature Tourism Park. The marine cadastre classes were analyzed for their alignment with the marine management classes/blocks in the Pulau Weh Nature Tourism Park using an alignment logical matrix and overlay analysis. The field inventory results identified 7 marine cadastre classes in the marine conservation area of Pulau Weh Nature Tourism Park. The alignment classification of marine cadastre classes with the marine management classes/blocks in Pulau Weh Nature Tourism Park indicates that the aligned class covers an area of 476.26 hectares (9.07% of 5,247 hectares), the non-aligned class covers 441.08 hectares (8.41% of 5,247 hectares), and the transition class covers 4,329.75 hectares (82.52% of 5,247 hectares).Keywords:Marine CadastreCompatibilityAlignment logical matrixOverlay analysisNature Tourism Park